Interfaith Dialogue, Social Interaction, and Islamophobia Solution in Talang Benuang Village, Bengkulu, Indonesia - Rini Fitria, Ari Wibowo, Nuraida (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
This study aimed to find out the solutions in various religious conflicts that occur in Indonesia using the educational psychology of communication and social interaction in the Talang Benuang, Bengkulu communities with different religions, ethnicities, and races. The research method used a qualitative descriptive explanatory approach. The determination of informants used purposive sampling. The researchers collected data by snowball sampling. Research findings: educational psychology with a communication strategy which was carried out by division of residential locations, increasing tolerance, processing verbal and nonverbal messages, selecting and assigning communicators, setting and composing messages, managing differences between religious communities